Mechanical and thermal properties of recycled polypropylene bamboo fibre-reinforced composites - Indah Widiastuti; Devan Hidayat Pratama; Mohamad Lukmanul Hakim; Danar Susilo Wijayanto; Budi Harjanto (Institute of Advanced Engineering and Science, 2023)
In this article, a kind of green composite was prepared from recycled polypropylene (r-PP) which was further reinforced with various loadings of chemically modified bamboo fibres. Effects of bamboo fibre loading on the mechanical and thermal properties of r-PP/bamboo composites were studied. Those properties were characterized by tensile testing, impact testing, thermogravimetric analysis (TGA), and differential scanning calorimeter (DSC). Standardized test specimens with 0%, 10%, 20%, and 30% mass fractions of bamboo fibre were obtained by an extrusion process which was then finalized on injection molding. The experiment revealed the tensile strength and strain of the composite become greater with the increase of bamboo fraction in the ultimate value of 20% mass fraction. The composite with 10% bamboo fibre loading recorded the highest value of impact strength. Meanwhile, it was evident that the presence of bamboo fibre decreased the thermal stability of recycled polypropylene materials. Therefore, this composite material may find good potential for semi-structural loading applications in relatively low-exposure working.